Detection of Trypanosoma lewisi from rodents residing in the densely populated residential regions along the coastal areas of Banyuwangi Sub District, Indonesia - April Hari Wardhana; Frenky Laksana Putra; Aditya Yudhana; Dyah Haryuningtyas Sawitri; Ening Wiedosari; Mujiyanto Mujiyanto; Swastiko Priyambodo; Mufasirin Mufasirin; Penny Humaidah Hamid; Yudhi Ratna Nugraheni; Aan Awaludin; Priyono Priyono; et al. (Open Veterinary Journal, 2024)
Background: Extensive attention has been devoted to studies of Trypanosoma lewisi in rodents ever since it became recognised as a zoonotic pathogen known as atypical human trypanosomiasis. Regrettably, although T. lewisi infections of small mammals remain significant public health concerns for humans, there is a lack of comprehensive study in Indonesia. Aim: The aim of the study was to detect T. lewisi from rodents residing in the densely populated residential regions along the coastal areas of Banyuwangi Sub District. Methods: A total of 169 rodents were captured across three villages of Kampung Mandar, Lateng and Kepatihan, using rat single live traps. After being euthanized and identified, the blood samples were collected from each rodent via cardiac puncture. Subsequently, the samples were subjected to native (direct blood microscopic examination), microscopic blood smear examination, and molecular analyses utilizing TRYP1S-TRYP1R (623 bp) and LEW1S-LEW1R (220 bp). Results: The results demonstrated that two species of rodents were successfully captured: Rattus norvegicus (65.68%) and Rattus tanezumi (34.32%). Based on the native and microscopic blood smear examinations, the prevalence of T. lewisi across three villages was 23.08% and 24.26% for molecular analysis employing both primers, respectively. The highest prevalence was found in Kampung Mandar Village (31.18%), followed by Kepatihan (16.67%) and Lateng Villages (15.71%). Conclusion: Statistical analysis revealed that T. lewisi was more prevalent in R. tanezumi compared to R. norvegicus. In terms of sex, no statistically significant distinction was observed between female and male infected rodents of either species (p>0.05), indicating both species can serve as a source of T. lewisi for humans in the surveyed villages. [Open Vet J 2024; 14(8.000): 1808-1818]